Detection and Confirmation of Deafness-Causing Copy Number Variations in the STRC Gene by Massively Parallel Sequencing and Comparative Genomic Hybridization. (November 2016) - Moteki, Hideaki; Azaiez, Hela; Sloan-Heggen, Christina M.; Booth, Kevin; Nishio, Shin-ya; Wakui, Keiko; Yamaguchi, Tomomi; Kolbe, Diana L.; Iwasa, Yoh-ichiro; Shearer, A. Eliot; Fukushima, Yoshimitsu; Smith, Richard J.H.; et al.
Objective: Copy number variations (CNVs), a major cause of genetic hearing loss, most frequently involve the STRC gene, located on chr15q15.3 and causally related to autosomal recessive non-syndromic hearing loss (ARNSHL) at the DFNB16 locus. The interpretation of STRC sequence data can be challenging due to the existence of a virtually identical pseudogene, pSTRC, that promotes complex genomic rearrangements in this genomic region. Targeted genomic enrichment with massively parallel sequencing (TGE+MPS) has emerged as the preferred method by which to provide comprehensive genetic testing for hearing loss. We aimed to identify CNVs in the STRC region using established and validated bioinformatics methods. Methods: We used TGE+MPS to identify the genetic cause of hearing loss. The CNV results were confirmed with customized array comparative genomic hybridization (array CGH). Results: Three probands with progressive mild to moderate hearing loss were found among 40 subjects with ARNSHL to segregate homozygous STRC deletions and gene to pseudogene conversion. Array CGH showed that the deletions/conversions span multiple genes outside of the exons captured by TGE+MPS. Conclusion: These data further validate the necessity to integrate the detection of both simple variant changes and complex genomic rearrangements in the clinical diagnosis of genetic hearing loss.